2018
DOI: 10.1038/s41545-018-0011-0
|View full text |Cite
|
Sign up to set email alerts
|

Review of low-cost point-of-use water treatment systems for developing communities

Abstract: For communities in developing countries, the majority of drinking water-related issues are due to pathogens from poor sanitation, resulting in infection and diarrhea. One cause of this is that these communities often do not have access to centralized water treatment facilities. Point-of-use (POU) systems are key solutions for treating water in developing communities; they are typically user-friendly, low cost, low maintenance, and grid-independent. Importantly, they treat and reduce the number of pathogens in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(95 citation statements)
references
References 79 publications
0
86
0
1
Order By: Relevance
“…Chaidez et al (2016) developed a lowcost gravity ultrafiltration point-of-use for the treatment of wastewater for the waterborne gastrointestinal pathogen in rural communities of Mexico. Some point-of-use technologies have also been previously developed, especially for developing communities to remove selected waterborne pathogens (Pooi and Ng, 2018) and enteric viruses in the water systems (Gerba et al, 2018). Since preliminary investigations have suggested the oxidants like chlorine, ozonation, and UV irradiation have the potential to inactivate the SARS-CoV-2 in a water environment (Rosa et al, 2020;Wang et al, 2020c;Quevedo-león et al, 2020).…”
Section: Development and Use Of The Point-of-use Device For Virus Decmentioning
confidence: 99%
See 1 more Smart Citation
“…Chaidez et al (2016) developed a lowcost gravity ultrafiltration point-of-use for the treatment of wastewater for the waterborne gastrointestinal pathogen in rural communities of Mexico. Some point-of-use technologies have also been previously developed, especially for developing communities to remove selected waterborne pathogens (Pooi and Ng, 2018) and enteric viruses in the water systems (Gerba et al, 2018). Since preliminary investigations have suggested the oxidants like chlorine, ozonation, and UV irradiation have the potential to inactivate the SARS-CoV-2 in a water environment (Rosa et al, 2020;Wang et al, 2020c;Quevedo-león et al, 2020).…”
Section: Development and Use Of The Point-of-use Device For Virus Decmentioning
confidence: 99%
“…Also, some studies reported that SARS-CoV-2 loses its infectivity very quickly in wastewater (Venugopal et al, 2020;Annalaura et al, 2020). Nonetheless, other waterborne diseases contracted through the consumption of contaminated water such as diarrhea and gastroenteritis are rampant in low-income countries (Pooi and Ng, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is easy to operate, versatile and can be easily incorporated into current wastewater treatment technologies. Current researches are now geared towards the engineering of alternative hybrid adsorbents to the expensive activated carbon, and which have high pollutant binding capacities, low-cost with potentials for large scale treatment of wastewater (Pooi and Ng 2018), high stability and ease of operation (Abdus-Salam and Adekola 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Chlorine is the most widely used disinfectant in drinking water treatment due to its availability, low cost, and broad spectrum antimicrobial efficacy (Rodriguez and Serodes, 2001;Farghaly et al, 2013;Kumari and Gupta, 2015). Decentralized point-of-use (POU) drinking water treatment systems typically utilize alternative disinfectant solutions (Mbilinyi et al, 2005;Peter-Varbanets et al, 2009;Domènech, 2011;Attisani, 2016;Carratalà et al, 2016;Pooi and Ng, 2018) or chlorine release tablets (Jain et al, 2010;Werner et al, 2016), rather than conventional chlorination solutions (i.e., NaOCl) for the production of biologically safe water. Alternatives to conventional chlorination are adopted due to quicker disinfection times, ease of transport and storage (Clasen and Edmondson, 2006;Jain et al, 2010).…”
Section: Introductionmentioning
confidence: 99%